Bio preservation capacity of potentially probiotic Lacticaseibacillus strains in fermented sausage - Bertuci, Marcello Lima [UNESP]; Alves Junior, Carlos Alberto [UNESP]; Souza, Camila Vespúcio Bis [UNESP]; Penna, Ana Lúcia Barretto [UNESP]; da Silva Barretto, Andrea Carla [UNESP] (Oxford University Press (OUP), 2023)
Bio preservation constitutes a well-acknowledged natural method for controlling the growth of undesirable bacteria in meat products. The aim was to evaluate four different potentially probiotic Lacticaseibacillus strains as bio preservatives and their application in fermented meat sausage. The strains were inoculated for 24 h and used a concentration of 0.1% of the total mass into which it was directly inserted. Regarding the inhibition zone, only the commercial strains exhibited effect on the tested pathogens. They also displayed better growth results on MRS medium, which simulates meat product additives, during the 24-h period. The pH, sodium nitrite and sodium chloride proved to be limiting factors for the growth of the potentially probiotic Lacticaseibacillus strains. Lc. paracasei BGP1 significantly reduced water activity and pH – both fundamental factors for food conservation- when incorporated. Lc. paracasei BGP1 demonstrated its efficacy as bio preservative for use in fermented meat sausage. Technological parameters were evaluated, showing positive responses to the application of acid lactic bacteria. These results indicate the potential of lactic acid bacteria to inhibit certain microorganisms, offering a perspective on inhibition when used in fermented meat products. Hence, further studies could be conducted, primarily concerning Listeria sp.
Keywords: Acid lactic bacteria; Fermentation; Screening